Congenital short bowel syndrome: a rare cause of neonatal intestinal obstruction. Issue 9 (September 2020) - Zain, Mostafa; Abdelkader, Mansour; Azab, Ahmed; Kotb, Mostafa
Congenital short bowel syndrome (CSBS) is an uncommon gastrointestinal disorder in which an unclear aetiology causes considerable intrauterine reduction in small bowel length. As a result of reduced absorptive intestinal length, chronic diarrhoea, vomiting, and consequently, failure to thrive are likely. We report a case of CSBS in a 26-day-old girl who had malrotation and a short bowel with a length of bowel from the pylorus to the ileocecal junction of approximately 40 cm. The patient underwent Ladd's procedure, but she is still dependent on parenteral nutrition.